Terjemahan dan validasi psikometrik versi Indonesia dari Skala Pengendalian Perhatian (ATTC) dalam konteks bola basket. - Rahmadani, Ahmad; Candra, Oki; Perdima, Feby Elra; Gazali, Novri; Setiawan, Edi (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2025)
Attention control is vital for athletic performance, particularly in high-pressure situations requiring quick decisions and sustained focus. The Attention Control Scale (ATTC) is a concise self-report measure of attentional skills, yet no validated Indonesian version exists—limiting sport psychology assessment in the country. This study translated the ATTC into Indonesian using a forward–backward translation procedure and evaluated its psychometric properties among 300 collegiate basketball athletes in Pekanbaru, Indonesia. Data were collected via online and offline self-administered questionnaires and analysed with SPSS 26 and AMOS 24, including descriptive statistics, internal consistency, test–retest reliability, and confirmatory factor analysis (CFA). CFA confirmed the two-factor structure—Focusing Attention and Shifting Attention—with good fit indices (CFI = 0.93; TLI = 0.91; RMSEA = 0.065; SRMR = 0.057). The scale showed strong internal consistency (α = 0.86) and high test–retest reliability (ICC = 0.89). While the ATTC is a self-report tool and not a substitute for objective tests, it offers a practical, culturally adapted instrument for coaches, sport psychologists, and educators to assess and enhance athletes’ attentional readiness.